Relapsed and refractory yolk sac tumor of the peritoneum (mesentery): A case report and literature review - Zhou, Xue; Zhao, Lanbo; Feng, Xue; Pan, Zhenni; Bin, Yadi; Zhang, Siyi; Li, Min; Guo, Miao; Hou, Huilian; Li, Qiling (Frontiers in Oncology, 2022)
Background: Extragonadal yolk sac tumor (YST) of peritoneum is a rare malignancy. Case Description: A 37-year-old Chinese woman was admitted to hospital with a 3-month abdominal pain 4 years ago. Alpha-fetoprotein was 228,499.0 ng/mL. Computed tomography scan revealed a massive mass in the left lower abdomen. Exploratory laparotomy exposed a huge mesenteric mass. Then, mesenteric tumor resection, partial sigmoidectomy, and single-lumen fistula of sigmoid colon were performed. Postoperative pathologic diagnosis reported a stage Ⅳ mesenteric YST. After surgery, the patient received 6 courses of BEP (bleomycin, etoposide, and cisplatin) chemotherapy. Seven months later, the patient underwent stoma reversion of sigmoid colon and received another 2 courses of BEP chemotherapy. Three months after the last chemotherapy, liver metastases were diagnosed. She subsequently underwent 3 surgeries, radiotherapy for liver metastases, and multiple tiers of palliative chemotherapies, including TP (docetaxel and carboplatin), VIP (ifosfamide, cisplatin, and etoposide), TIP (paclitaxel, ifosfamide, and cisplatin), and so on. After the third surgery (left hepatic lesion resection and right iliac lymph node resection), she received 4 cyclic chemotherapies of BEP´ (boanmycin, etoposide, and cisplatin) without pulmonary toxic side effects. Conclusion: Postoperative histopathology and immunohistochemistry are gold standards for the diagnosis of peritoneal YST. The standard first-line treatment is surgery plus BEP chemotherapy. Second-line therapy regimens and above, including VIP and TIP, improve the prognosis of recurrent germ cell tumors. This relapsed and refractory patient with peritoneal YST benefits from the secondary BEP´ chemotherapy.